Modern Sufis and the state: the politics of Islam in South Asia and beyond - Ewing, Katherine Pratt; Corbett, Rosemary R. (Religion, culture, and public life, 2020)
Frontmatter -- Contents -- Acknowledgments -- Note on Transliteration -- Introduction. Sufis and the State: The Politics of Islam in South Asia and Beyond -- 1. Anti-Colonial Militants or Liberal Peace Activists? The Role of Private Foundations in Producing Pacifist Sufis During the Cold War -- 2. From Taṣawwuf Modern to Neo-Sufism: Nurcholish Madjid, Fazlur Rahman, and the Development of an Idea -- 3. Beyond Barelwiism: Tahir-ul- Qadri as an Example of Trends in Global Sufism -- Commentary on Part I: Ambiguities and Ironic Reversals in the Categorization of Sufism -- 4. Is the Taliban Anti-Sufi? Deobandi Discourses on Sufism in Contemporary Pakistan -- 5. Sufism Through the Prism of Sharia: A Reformist Barelwi Girls’ Madrasa in Uttar Pradesh, India -- 6. Lives of a Fatwa: Sufism, Music, and Islamic Reform in Kachchh, Gujarat -- Commentary on Part II: Sufis, Sharia, and Reform -- 7. “A Way of Life Rather Than an Ideology?”: Sufism, Pīrs, and the Politics of Identity in Sindh -- 8. Sufi Politics and the War on Terror in Pakistan: Looking for an Alternative to Radical Islamism? -- 9. “Our Vanished Lady”: Memory, Ritual, and Shiʿi-Sunni Relations at Bībī Pāk Dāman -- Commentary on Part III: The Problems and Perils of Translating Sufism as “Moderate Islam” -- 10. Is All Politics Local? Neighborhood Shrines and Religious Healing in Contemporary India -- 11. Sufi Healing and Secular Psychiatry in India -- 12. Sufi Sound, Sufi Space: Indian Cinema and the Mise-en- Scène of Pluralism -- Commentary on Part IV: Sufism in Indian National Spaces -- Conclusion: Thinking Otherwise -- Notes -- Glossary -- Bibliography -- List of Contributors -- Index -- RELIGION, CULTURE, AND PUBLIC LIFE